The split notochord syndrome with dorsal enteric fistula, meningomyelocele and imperforate anus - Hüseyin Dindar; Turan Kanmaz; Murat Çakmak; Çağrı Savaş; Selçuk Yücesan (The Turkish Journal of Pediatrics)
A male infant was referred to our department because of lumbosacral meningomyelocele, dorsal enteric fistula and imperforate anus. The mother had received a parenteral drug containing estradiol benzoate and progesterone for inducing abortion in the first trimester. She also used an anal pomade containing triamcinolone and lidocaine-HCI during the pregnancy for hemorrhoids.